The upcycling of recycled polyamide 6 via novel chain extenders - Yap, Pearleen Pin Xiu (Nanyang Technological University, 2025)
As the use of plastics such as polyamide 6 (PA6) continues to grow with no indication of a decline, there is a pressing need for more effective strategies such as the use of recycled alternatives. However, recycled alternatives such as mechanically recycled polyamide 6 (rPA6) often exhibit inferior mechanical properties and are unable to be reused for their original purpose. As such, this dissertation aims to improve the properties of rPA6. Chain extenders were typically used to improve the properties of polymers like PA6. However, traditional chain extenders (i.e. caprolactam & oxazoline) were ineffective in improving the properties of PA6, compared to maleic anhydride (MAH) & epoxy chain extenders. Synergistic improvement was observed when a combination of traditional chain extenders was used in PA6. The goal of this research is to understand why there is a synergy between some MAH and epoxy chain extenders to improve the mechanical properties of rPA6 through an efficient reactive extrusion process.